Nori species (Rhodophyta, Bangiales): a brief review of nutritional and economic potential in Brazil - Silva, Lana Lopes da [UNESP]; Obando, Johana Marcela Concha [UNESP]; Machado, Levi Pompermayer [UNESP]; Bueno, Guilherme Wolff [UNESP]; Santos, Thalisia Cunha dos (Univ Federal Ceara, Dept Geol, 2025)
The species Porphyra, Pyropia, and Neopyropia are widely cultivated and consumed worldwide due their valuable nutraceutical properties. These red algae are rich in essential macronutrients, including carbohydrates, lipids, proteins, and minerals. They also contain bioproducts beneficial to human health, such as pigments (phycobiliproteins), phenolic compounds, polyunsaturated fatty acids (PUFAs), and polysaccharides, which exhibit antioxidant, anti-inflammatory, neuroprotective, and anti-obesity activities. These algae are particularly important as edible seaweeds, being most notably used in the production of Nori. This review examines recent research on the nutritional value of Nori species, based on 17 selected articles. The data were organized according to protein, carbohydrate, lipid, and ash content. Additionally, we explore the bioactive compounds found in these species, such as pigments, fatty acids, and phenolic compounds. Our discussion also emphasizes the economic potential of Nori in Brazil. Despite the country's rich biodiversity, Brazil remains a major importer of algae for human consumption. However, there is significant potential for expanding its presence in the aquaculture sector, creating opportunities for the cultivation of Nor i species. These growing prospects could pave the way for the sustainable exploitation of this resource in both national and global markets.
Keywords: Nori; Rhodophyta; Nutraceutical potential; Food bioproducts